Self-financing water supply and sanitation services - Terence R. Lee; Andrei Jouravlev (CEPAL Review, 1992)
Financing investments in urban water supply and sanitation has been a perennial problem in all countries of Latin America and the Caribbean. The issue has increased in significance with the need to provide sewage treatment to reduce the gross pollution of many water bodies and to lessen the threat from waterborne diseases. In this paper, the authors explore, through a statistical analysis, the practicability of financing water supply and sanitation services from income generated by the tariffs. Particular emphasis is placed on the possibility of the whole population paying for sanitation services: an issue of some importance given the unequal distribution of income in most cites of the region.